A Certain q-Sălăgean Differential Operator and Its Applications to Subclasses of Analytic and Bi-Univalent Functions Involving (p, q)-Chebyshev Polynomial (Contemporary Mathematics, 2024)
In the present investigation, we make use of the q-analogue of the Sălăgean differential operator and introduce a new subclass of analytic and bi-univalent functions SΣη,μ involving the (P, Q)-Chebyshev polynomials. Furthermore, we derive coefficient inequalities and obtain the Fekete-Szegö problem for this new function class f ∈ SΣη,μ of functions.
Keywords: bi-univalent functions; (P,Q)-chebyshev polynomials; sălăgean differential operator